Functional Constipation in Children from Urban Communities: Prevalence and Associated Factors - Mengdian ZHANG, Shuang YU, Yuchun LIU, Jing DING (Zhongguo quanke yixue, 2022)
Background Functional constipation (FC) is highly prevalent with complex associated factors in children, posing great health risk to the affected children. So far, the results of studies on the prevalence of FC and its influencing factors vary widely, and those focusing on FC in urban children in China are relatively few. Objective The purpose was to investigate the prevalence and influencing factors of FC in children in urban communities, so as to provide data support for establishing a database of FC in children in the community and for carrying out standardized, multidisciplinary and continuous management of FC in children in the community. Methods Children aged 6 to 48 months who were registered as recipients of health services delivered by Yuetan Community Health Center, Beijing were selected from the Beijing Maternal and Child Healthcare Information System (Phase 2) during the period from April to July 2021. A questionnaire designed by our research group was used to survey the primary guardians of the included children, focusing on questions related to defecation habits prepared according to the RomeⅣ criteria for FC in the Childhood Functional Gastrointestinal Disorders: Neonate/Toddler issued in 2016, and factors possibly influencing FC including history of allergies, family history of constipation, mode of delivery, feeding practices, appetite, eating habits, daily water intake, frequency of physical activity, and family parenting practices. In total, 1 458 guardians attended the survey, and children of the 1 264 (86.69%) guardians who handed in responsive questionnaires were finally included for analysis. Results The overall prevalence of FC was 9.89% (125/1 264) . Specifically, the prevalence of FC in age groups of 6 to 12, 13 to 36, and 37 to 48 months was 10.39% (16/154) , 8.75% (69/789) , and 12.46% (40/321) , respectively, demonstrating no significant difference in FC prevalence by age group (P>0.05) . The results of multivariate Logistic regression analysis showed that allergy history and feeding practices were influential factors for FC in 6-12-month-old children (P<0.05) , allergy history, feeding practices and parenting style were influential factors for FC in 13-36-month-old children (P<0.05) , and allergy history and parenting style were influential factors for FC in 37-48-month-old children (P<0.05) . Conclusion The prevalence of FC in 6-48-month-old children in urban communities is high, which is associated with multiple preventable and controllable factors, suggesting that the prevention of FC in this age group of children should be carried out in accordance with individual factors, family relationship, and social environment.